Nicolas Da Silva, Instituer la performance. Une application au travail du médecin - Nicolas Da Silva (Revue de la Régulation)
Health care relation is exemplary of the logic of performance witch illustrates a major change in human resources management strategies. Historically, negotiations between the State and physicians exclusively focused on prices. However, since the beginning of the 90’s, public regulation is carried out through professional norms. The introduction of pay-for-performance in France is the ultimate stage in this metrological turning point defined by a numerically-based assessment of medical work. In an institutionalist viewpoint, our thesis seeks to question the relevance of this reform which aims at instituting performance. We show that this project is neither effective nor efficient. It is implemented regardless of the patients’ interests. Yet, in the contemporary neoliberalism spirit, health is associated with a good as any other, surrounding which it is possible to generate competition among producers and consumers.